Effect of protein and lipid levels in diets for adult sea urchin Paracentrotus lividus (Lamarck, 1816) - Baião, Luís F. (2019)
Paracentrotus lividus gonads are considered a prized seafood delicacy due to its organoleptic features. The increasing market demand for sea urchin depleted several wild stocks, thus aquaculture can play an important role in supplying high-quality animals. Nevertheless, the success of this activity largely depends on the development of nutritionally balanced diets capable of producing excellent gonads. In this study, four extruded diets formulated with low or high protein (30 and 50% dry matter (DM), LP and HP, respectively) and lipid (6 and 11% DM, LL and HL, respectively) levels were fed to wild-caught individuals (4.5 cm diameter) for 15 weeks. Twelve homogeneous groups of 15 individuals were randomly distributed by mesh cages (45 urchins/m(2)) within 250 L tanks in a recirculating aquaculture system (RAS) at 18 degrees C and a 12 L:12 D photoperiod regime. Sea urchins fed the LP/LL diet were compared to wild specimens with similar maturation stage. All experimental diets were well accepted by sea urchins and resulted in similar final body weight (42-43 g). No significant differences were observed in specific growth rate or protein efficiency ratio among diets. The HP diets led to a decrease of dry matter and energy intake resulting in the lowest feed conversion ratio (FCR). Weight gain, whole body composition and nutrient gain remained similar among dietary treatments. The gonad somatic index (GSI) varied between sex but was similar among dietary treatments (19-23%) and was higher than values observed in wild specimens (6-7%). Females had significantly higher total concentration of carotenoids than males, irrespectively of the dietary treatments. Dietary treatments and sex did not affect gonad texture (firmness and resilience) or colour parameters (brightness, redness, yellowness, chroma or hue angle), but affected gonad composition. Total carotenoid content in gonads was not affected by diets and resulted in lower values compared to wild specimens. These had higher levels of echinenone, beta-cryptoxantin and beta-carotene and showed higher redness and firmness values when compared to the LP/LL diet, irrespectively of the sex. Gonad lipid content and n-3 PUFA were higher in female than in male, whilst protein content showed an opposite trend, suggesting some sex related differences in the metabolic use of nutrients. This study clearly shows that it is possible to enhance sea urchin gonad yield in relation to wild animals in a RAS at 18 degrees C. All diets were effective in promoting gonad growth, but the diet with the lowest protein (30% DM) and lowest lipid (6% DM) level resulted in the highest gonad yield in both sexes.